Sleep Hygine Dan Aroma Terapy Lavender Terhadap Kualitas Tidur Remaja Laki Laki - Liza Erawati Siregar; Emi Yuliza; Irma Herlina (Jurnal Ilmiah Kesehatan Mandira Cendikia, 2024)
The prevalence of sleep Hygiene in teenagers varies, according to previous research showing that sleep quality at the age of 18 to 80 years is 36% of poor quality. Data in Indonesia shows that the majority of teenagers' sleep quality is inadequate, namely 63%. To determine the effectiveness of providing sleep hygiene and lavender aroma therapy on the sleep quality of adolescent boys in Rt 02, Meruyung Limo District, Depok in 2023. This type of research is analytical research with a quasi-experimental method, and a pre-test and post-test design. The sample used in this research was 23 respondents, using a purposive sampling technique. Place of analysis in this study uses the Wilcoxon test because the data is not normally distributed. Before being given the intervention, 19 (82.6%) teenagers had moderate sleep quality, and 4 (17.4%) teenagers had poor sleep quality. After being given the intervention, it was found that 23 (100%) teenagers (100%) had good sleep quality. In the Wilcoxon test, a p-value of 0.000 was obtained, giving sleep hygiene and lavender aroma therapy improved the sleep quality of teenagers. Providing sleep hygiene and lavender aroma therapy is effective in improving the quality of sleep in teenagers. It is hoped that it can be used as an intervention to improve the quality of sleep for teenagers by utilizing sleep hygiene and lavender aromatherapy in non-pharmacological treatment